2018
DOI: 10.1158/0008-5472.can-17-1434
|View full text |Cite
|
Sign up to set email alerts
|

MBD2 Ablation Impairs Lymphopoiesis and Impedes Progression and Maintenance of T-ALL

Abstract: Aberrant DNA methylation patterns in leukemia might be exploited for therapeutic targeting. In this study, we employed a genetically deficient mouse model to explore the role of the methylated DNA binding protein MBD2 in normal and malignant hematopoiesis. MBD2 ablation led to diminished lymphocytes. Functional defects of the lymphoid compartment were also observed after reconstitution of MBD2-deficient hematopoietic stem cells (HSC). In an established model of Notch1-driven T-cell acute lymphoblastic leukemia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…ChIP assays were performed as previously described. 19 Antibody anti-MBD2 was from Bethyl Laboratories, and isotypic IgG from Beyotime Biotechnology. The DNA Purification Kit (TIANGEN, Beijing, China) was used to purify the coprecipitated DNA.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP assays were performed as previously described. 19 Antibody anti-MBD2 was from Bethyl Laboratories, and isotypic IgG from Beyotime Biotechnology. The DNA Purification Kit (TIANGEN, Beijing, China) was used to purify the coprecipitated DNA.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…[16][17][18] Our previous study defined essential roles for MBD2 in lymphopoiesis and Tcell acute lymphoblastic leukaemia (T-ALL) and suggested MBD2 as a candidate therapeutic target in T-ALL. 19 The expression of MBD2 was high in CML-BP patients. 20 Therefore, we can speculate that MBD2 may be a selective target for CML therapy.…”
Section: Introductionmentioning
confidence: 96%
“…Among these proteins, MBD2 has been shown to have the highest binding activity to methylated CpG DNA. Therefore, MBD2 has been recognized to be involved in the pathogenesis of tumorigenesis (19), autoimmunity (20,21), ischemic injury (22), obesity (17), and neuronal degeneration (23).…”
Section: Introductionmentioning
confidence: 99%
“…To further follow CD74 regulated cascades, RNA sequencing (RNAseq) analysis of gene expression in WT and CD74 −/− CD34-LSK cells was performed. RNAseq revealed that CD74 regulated the expression of transcription factors including KLF4, KLF2, and E2F2, and altered the expression of pathways induced by transcription factors such as IRF8, MDB2, and CEBPA, which are known to regulate HSCP maintenance ( S5B Fig) [39][40][41][42][43][44]. The RNAseq also revealed a regulation of the ITGB2 and ITGB3 pathways.…”
Section: Plos Biologymentioning
confidence: 96%